2022
DOI: 10.1021/jacs.2c07893
|View full text |Cite
|
Sign up to set email alerts
|

Natural Sunlight Photocatalytic Synthesis of Benzoxazole-Bridged Covalent Organic Framework for Photocatalysis

Abstract: Although natural sunlight-mediated photocatalysis is a clean, efficient, and green approach to access organic products, its application in the synthesis of covalent organic frameworks (COFs), however, is still unprecedented. Herein, we first report the sunlight photocatalytic synthesis of COF under ambient conditions. Furthermore, this “window ledge” reaction generated benzoxazole-linked COF is stable and can be applied as a reusable photocatalyst to highly promote visible-light-driven aerobic oxidation of sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 39 publications
0
50
0
Order By: Relevance
“…Indeed, LCU-20 exhibited superior photocatalytic activities under white LED light conditions for selective oxidation of sulfides than those of the reported results under blue LED light. 15,17…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, LCU-20 exhibited superior photocatalytic activities under white LED light conditions for selective oxidation of sulfides than those of the reported results under blue LED light. 15,17…”
Section: Resultsmentioning
confidence: 99%
“…9,10 Photocatalytic oxidation of sulfides features the advantages of simple operation, mild reaction conditions, low cost, and environmental friendliness, providing an alternative strategy. 11–14 Until now, various photocatalysts including organic materials 15 and metal complexes 16 have been investigated for the aerobic oxidation of sulfides and have made tremendous progress. For instance, Zhang's group confirmed that electron-deficient triazine-based COFs could afford high conversion and selectivity because the material can not only facilitate the generation and separation of charges, but also enrich the photocatalytically active sites.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the construction of high-quality chiral COFs requires the rational optimization of reaction conditions to balance crystallinity and optical purity. Fortunately, progress has been achieved in the synthesis of COFs under ambient conditions, and this field has now expanded to include chiral COFs . Additionally, protective groups, modulators, or tandem reactions may effectively increase COF crystallinity by decelerating framework formation, and this approach is expected to be extended to the MCR-based synthesis of chiral COFs in the near future.…”
Section: Summary and Further Challengesmentioning
confidence: 99%
“…Although COFs can act as a replacement for the homogeneous photocatalyst analogues, like inorganic metal-complexes[Ru­(bpy) 3 ]­(PF 6 ) 2 and Ir­(ppy) 3 , or organic dyes, such as 4CzIPN, Eosin Y, and acridinium, they have mainly been employed in water splitting, carbon dioxide reduction, and hydrogen evolution reactions . A few examples in organic synthesis include oxidation, oxidative hydroxylations, C–H functionalization, C–C, C–N, and, C–S cross-coupling reactions using metal-anchored (primarily) COF photocatalysts. However, metal-anchored COFs might contaminate the products with a trace amount of metal and suffer from reusability issues.…”
Section: Introductionmentioning
confidence: 99%